Cogan's syndrome with pyoderma gangrenosum: management of two uncommon disorders with aggressive presentation in a patient. (19th June 2018) - Chua, Ezolene Pei-Chin; Mallett, Richard B; Dahiya, Sandeep
Abstract : Pyoderma gangrenosum (PG) coexisting with Cogan's syndrome (CS) is uncommon, although cutaneous manifestations are known to develop in CS. A middle-aged white female patient had chronic relapsing PG requiring ciclosporin and prednisolone. Despite receiving optimal doses of ciclosporin and prednisolone, she developed acute vestibulo-auditory symptoms as a result of CS. Ciclosporin was switched to methotrexate and prednisolone was increased. However, she continued to develop acute scleritis, requiring methylprednisolone pulses, and still had further flares of PG. Her methotrexate was held off when she developed severe pneumonia and she then received a trial of intravenous immunoglobulins (IVIG) for her recurrent leg ulcers. Unfortunately, she failed to respond to IVIG. Her ulcers eventually responded to six doses of monthly intravenous cyclophosphamide induction. Although CS is not an antineutrophil cytoplasmic antibodies (ANCA)-associated vasculitis, we used pulse cyclophosphamide, based on the experience of cyclophosphamide efficacy in severe ANCA-associated vasculitis (AAV). Following induction, both diseases currently remain under control with azathioprine as maintenance treatment.